A new immigration intelligence system to combat transnational organized crime in Latin America - Abásolo Dupont, Ramón (2024)
Migration Intelligence involves the preparation of reports that reveal the challenges faced by countries in the field of migration, particularly concerning the fight against organized crime. This is accomplished through a periodic report on the current and prospective situation of irregular immigration or an alert triggered by the detection of a new modus operandi of transborder crime. In Europe, these documents are crafted using the CIRAM risk analysis methodology (Common Integrated Risk Analysis Model), which necessitates the training of specialized analysts in migration intelligence and the use of advanced data analysis tools for Comprehensive Border Management. This article focuses on presenting and evaluating the intended implementation of the Migration Intelligence Network, initiated by EUROFRONT, at four border crossings in the region: Rumichaca (between Colombia and Ecuador), Desaguadero (between Peru and Bolivia), Triple Frontier (between Argentina, Brazil, and Paraguay), and Aguas Blancas-Bermejo (between Argentina and Bolivia); as well as the potential implications for Peru.